2018
DOI: 10.1364/oe.26.034031
|View full text |Cite
|
Sign up to set email alerts
|

Secure and private NOMA VLC using OFDM with two-level chaotic encryption

Abstract: In this paper, we propose and demonstrate a secure and private non-orthogonal multiple access (NOMA) based visible light communication (VLC) system. Orthogonal frequency division multiplexing (OFDM) modulation is applied in the system and a two-level chaotic encryption scheme is further implemented, which can guarantee both the security of legitimate users against eavesdroppers and the privacy among all the legitimate users. An experimental demonstration with two legitimate users and one eavesdropper successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In Ref. [32], Yang et al proposed a NOMA-VLC system with a two-level chaotic encryption scheme. The results showed that this scheme can guarantee the security of legitimate users against eavesdroppers and privacy among all legitimate users.…”
Section: Related Workmentioning
confidence: 99%
“…In Ref. [32], Yang et al proposed a NOMA-VLC system with a two-level chaotic encryption scheme. The results showed that this scheme can guarantee the security of legitimate users against eavesdroppers and privacy among all legitimate users.…”
Section: Related Workmentioning
confidence: 99%
“…Chaos is a part of mathematics that reviews the behavior of a dynamic framework that is very sensitive to the initial condition, randomness, and unpredictability. In [4], the authors suggested a private nonorthogonal multiple-access visible-light communication system encryption based on nonlinear dynamical systems. The encryption scheme assures privacy among all legal users against attackers during communication.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is quite challenging to achieve high-speed and large-capacity VLC systems by utilizing low-cost COTS white LEDs. To overcome the bandwidth limitation, many capacityenhancing techniques have been proposed for VLC systems using COTS white LEDs so far, including frequency domain equalization (FDE) schemes for substantial extension of LED modulation bandwidth [11]- [13], spectral-efficient modulation formats such as orthogonal frequency division multiplexing (OFDM) using high-order quadrature amplitude modulation (QAM) constellations [14], [15], and multiple-input multipleoutput (MIMO) transmission [16], [17]. In particular, MIMO is a very natural and efficient way to improve the achievable capacity of an indoor VLC system, since multiple LEDs are commonly mounted in the ceiling of a typical indoor environment so as to obtain sufficient and uniform illumination [18].…”
Section: Introductionmentioning
confidence: 99%